Global knowledge mapping and emerging research trends in the microbiome and asthma: A bibliometric and visualized analysis using VOSviewer and CiteSpace - ZhiFeng Guo; LingHong Huang; SuMei Lai (Heliyon, 2024)
Background: Numerous prior studies have extensively highlighted the significance of the microbiome in association with asthma. While several studies have concentrated on the asthma microbiome in previous research, there is currently a lack of publications that employ bibliometric methods to assess this area. Methods: In this study, the Web of Science Core Collection database was utilized as the data source, and the SCI-EXPANDED index was employed to ensure that the retrieved data were comprehensive and accurate. All original research articles and review articles related to the correlation between asthma and the microbiome were systematically searched from the inception of the database until June 20, 2023. These articles were subsequently visualized and analyzed using VOSviewer and CiteSpace software. Results: A total of 1366 relevant publications were acquired, indicating a consistent annual increase in global publications in the field. The United States and China emerged as the top two contributors to international publications. Among prolific authors, Susan V. Lynch achieved the highest publication record, with Hans Bisgaard and Jakob Stokholm sharing the second position. The majority of publications concentrated on allergy-related and microbiome areas, with a few comprehensive journals standing out. Journals with 40 or more publications included the Journal of Allergy and Clinical Immunology, Allergy, Frontiers in Immunology, and PLOS One. The top 5 cited journals were the Journal of Allergy and Clinical Immunology, PLOS One, American Journal of Respiratory and Critical Care Medicine, Clinical and Experimental Allergy, and Nature. Upon analyzing keywords, high-frequency terms, such as asthma, gut microbiota, microbiome, children, childhood asthma, allergy, risk, exposure, inflammation, diversity, and chain fatty acids emerged as representative terms in the field. Conclusion: This study systematically presented a comprehensive overview of the literature regarding the association between asthma and the microbiome over the last two decades. Through a bibliometric perspective, the findings may assist researchers with a better understanding of the essential information in the field.